Vaccination concerns, beliefs and practices among Ukrainian migrants in Poland: a qualitative study - Maria Ganczak; Klaudia Bielecki; Marzena Drozd-Dąbrowska; Katarzyna Topczewska; Daniel Biesiada; Agnieszka Molas-Biesiada; Paulina Dubiel; Dermot Gorman (BMC, 2021)
Abstract Background Ukrainians numbering approximately 1.2 million are the largest migrant group in Poland. Data on vaccination coverage among migrants are not collected in EU, including Poland. Therefore, this qualitative study aimed to identify vaccination practices in this migrant group, to explore facilitators and barriers to vaccination and related access to Polish healthcare services. Methods In September 2019, a qualitative study of Ukrainian migrants (UMs) living in Szczecin, Poland, and recruited through a snowball sampling method, was conducted. Using a semi-structured topic guide, four focus groups were held with 22 UMs aged 18-45. Participants were asked about their attitudes towards vaccination in general with comparison between services in Poland and Ukraine. Following transcription and translation, a thematic analysis was conducted. Results Respondents were distrustful of Ukrainian vaccination policy, medical personnel and individual vaccines, however, they often returned to Ukraine for dental and gynaecological appoint-ments. While critical with regards to registering with Polish GPs practices, UMs were confident in health professionals, as well as vaccine delivery. Vaccines were perceived as safer and of better quality than in Ukraine. Difficulties in translating vaccination records were rarely reported, verbal communi-cation was not problematic due to language similarities. All UM parents reported vaccinating their children according to the Polish schedule. However, a significant number of adult UMs have not completed mandatory vaccinations, although they may have obtained false immunization certificates; according to UMs those can be obtained by bribing. Participants reported lower acceptance of the influenza vaccine, mainly due to perceptions around its importance; none had been vaccinated against influenza. None of UMs had heard of the HPV vaccine. UMs experienced challenges in accessing credible online vaccination information in Ukrainian, no official local health authority vaccination material existed either, except for information about measles. Conclusions This study pinpointed positive UM attitudes and practices regarding child vaccination in the Polish healthcare system and identified issues for improvement, such as adult vaccination. Health communication should be more tailored within UMs information delivery systems to enable migrants to make informed choices about vaccination. Further research is needed to better assess factors affecting vaccine uptake identified in this study.